Information communication technology and economic development learning from the Indian experience - Stough, Roger 1940-2019; Thatchenkery, Tojo (Edward Elgar, 2005)
Information Communication Technology and Economic Development reveals new insights regarding the complex process of globalization. It shows how the generation and circulation of intellectual capital in the US and India in ICT have led to greater productivity in the US while facilitating the economic development of India. Most industrialized nations now see the vast intellectual capital-based services that India provides at extremely competitive rates as key to their own national competitiveness in the global arena. The contributors' findings suggest that India's ICT-led growth will accelerate in the next ten years, launching India as a major global economic power next to the US and China
Includes bibliographical references and index
Keywords: Wirtschaftsentwicklung; Kommunikationstechnik; Indien; Telecommunication / India; Diffusion of innovations / India; Information services industry / India; Information technology / Economic aspects / India; India / Economic conditions / 1947-; Aufsatzsammlung